Struktur dan Prinsip Pendidikan Islam Dalam Membangun System Pendidikan Yang Holistik - Cindy Fatikasari Ibrahim; Syarifah Aini Kamilah; Fhirda Faiza; Opik Taupik Kurahman; Dadan Rusmana (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This research is motivated by the fact that Islamic education needs a holistic system to answer the challenges of the times while maintaining its fundamental values. This research aims to analyse the structure and principles of Islamic education in an effort to build a comprehensive and integrated education system. This research applies a normative juridical approach and descriptive analysis method, with data collected through literature study and documentation. The data obtained was analysed using qualitative data analysis techniques to deeply understand the concepts, principles and implementation of an Islamic education system that is relevant to the needs of modern society.